The impact of zero markup drug policy on patients' healthcare utilization and expense: An interrupted time series study - Zhu, Zheng; Wang, Junfeng; Sun, Yan; Zhang, Jiawei; Han, Peien; Yang, Li (Frontiers in Medicine, 2022)
Objective To curb the unreasonable growth of pharmaceutical expenditures, Beijing implemented the zero markup drug policy (ZMDP) in public hospitals in 2017, which focused on separating drug sales from hospital revenue. The purpose of this paper is to evaluate the impacts of ZMDP on healthcare expenditures and utilization for inpatients. Methods The study extracted the Beijing claims data from the China Health Insurance Research Association (CHIRA) database. Inpatients diagnosed with ischemic heart disease (IHD), chronic renal failure (CRF), and lung cancer (LC) were chosen for analysis. The study employed an interrupted time series to evaluate the impacts of ZMDP on healthcare expenditures and utilization. Results The total hospitalization expenses and healthcare insurance expenses of inpatients diagnosed with ischemic heart disease increased in long-term trends (β3=0.077). The Western medicine expenses for the treatment of inpatients diagnosed with ischemic heart disease significantly decreased by 1923.38 CNY after the reform(P<0.05). The Chinese medicine expenses of inpatients diagnosed with chronic renal failure instantaneously increased by 1344.89 CNY (P<0.05). The service expenses of inpatients diagnosed with ischemic heart disease and lung cancer instantaneously increased by 756.52 CNY (p>0.05) and 2629.19 CNY (p<0.05), respectively. However, there were no significant changes (P>0.05) in out-of-pocket expenses, medical consumables, imaging, and laboratory test expenses of inpatients diagnosed with ischemic heart disease, chronic renal failure, or lung cancer. The initiation of the intervention immediately increased the number of inpatient admissions with lung cancer (p<0.05). Conclusions The ZMDP was effective in reducing drug costs and optimizing the cost structures. However, the implementation of ZMDP alone may not be enough to relieve the patient's financial burden because the profit-driven behavior of healthcare providers remained. Policymakers are advised to take multiple and long-lasting measures to reverse the profit-driven behavior of public hospitals thoroughly.